Promoting or Preventing? The Influence of Artificial Intelligence Awareness on Employee Job Crafting - Xu, Feng; Qin, Jing; Zhang, Dayong (The Journal of applied behavioral science, 2025)
Artificial intelligence (AI) enhances employees’ work efficiency and significantly impacts their cognitive and psychological states. However, there remains limited research on the complex relationship between AI-driven changes in the work setting and employees’ job crafting. Therefore, this study applies the job demand–resource (JD-R) theory to test how AI awareness influences employees’ promotion- and prevention-focused job crafting. It further investigates the mediating roles of job insecurity and creative process engagement and the moderating role of AI knowledge. Based on the sample of 324 participants, the empirical results show that challenge appraisal toward AI indirectly promote promotion-focused job crafting through creative process engagement and inhibit prevention-focused job crafting through job insecurity. Conversely, hindrance appraisal toward AI indirectly promotes prevention-focused job crafting through job insecurity. Additionally, the positive effect of challenge appraisal on creative process engagement is strengthened by AI knowledge. Discussions are provided on both the theoretical and practical implications.